The Importance of Intrinsically Disordered Segments of Cardiac Troponin in Modulating Function by Phosphorylation and Disease-Causing Mutations - Papadaki, Maria; Marston, Steven B. (Frontiers in Physiology, 2016)
Troponin plays a central role in regulation of muscle contraction. It is the Ca2+ switch of striated muscles including the heart and in the cardiac muscle is physiologically modulated by PKA-dependent phosphorylation at Ser22 and 23. Many cardiomyopathy-related mutations affect Ca2+ regulation and/or disrupt the relationship between Ca2+ binding and phosphorylation. Unlike the mechanism of heart activation, the modulation of Ca2+-sensitivity by phosphorylation of the cardiac specific N-terminal segment of TnI (1-30) is structurally subtle and has proven hard to investigate. The crystal structure of cardiac troponin describes only the relatively stable core of the molecule and the crucial mobile parts of the molecule are missing including TnI C terminal region, TnI (1-30), TnI (134-149) (‘inhibitory’ peptide) and the C-terminal 28 amino acids of TnT that are intrinsically disordered. Recent studies over the years have been performed to answer this matter by building structural models of cardiac troponin in phosphorylated and dephosphorylated states based on peptide NMR studies. Now these have been updated by more recent concepts derived from molecular dynamic simulations treating troponin as a dynamic structure. The emerging model confirms the stable core structure of troponin and the mobile structure of the intrinsically disordered segments. We will discuss how we can describe these segments in terms of dynamic transitions between a small number of states with the probability distributions being altered by phosphorylation and by HCM or DCM-related mutations that can explain how Ca2+-sensitivity is modulated by phosphorylation and the effects of mutations.